2011
DOI: 10.1002/bdm.692
|View full text |Cite
|
Sign up to set email alerts
|

Loss aversion in the eye and in the heart: The autonomic nervous system's responses to losses

Abstract: The common view in psychology and neuroscience is that losses loom larger than gains, leading to a negativity bias in behavioral responses and Autonomic Nervous System (ANS) activation. However, evidence has accumulated that in decisions under risk and uncertainty individuals often impart similar weights to negative and positive outcomes. We examine the role of the ANS in decisions under uncertainty, and its consistency with the behavioral responses. In three studies, we show that losses lead to heightened aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
93
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 50 publications
23
93
2
1
Order By: Relevance
“…In fact, in research on description-and experience-based risky choice, its ability to explain actual behavior (choice) in monetary gambles has been questioned (see Erev et al, 2008;Hochman & Yechiam, 2011). At the same time, Hochman and Yechiam reported evidence that the possibility of losses results in increased autonomic arousal relative to the possibility of gains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in research on description-and experience-based risky choice, its ability to explain actual behavior (choice) in monetary gambles has been questioned (see Erev et al, 2008;Hochman & Yechiam, 2011). At the same time, Hochman and Yechiam reported evidence that the possibility of losses results in increased autonomic arousal relative to the possibility of gains.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of choice between monetary gambles, loss aversion suggests that because of people's sensitivity to losses relative to gains, most would not accept gambles with mixed symmetric outcomes (i.e., gaining or losing an amount x with the same likelihood). Empirical evidence, however, appears not to support this prediction (for a review see Hochman & Yechiam, 2011). Relatedly, in decisions from experience there is an ongoing debate about how to explain choices previously interpreted as indicative of loss aversion (e.g., Erev, Ert, & Yechiam, 2008).…”
Section: Do Losses Invoke More Search Than Gains?mentioning
confidence: 99%
“…This phenomenon is not limited to conscious psychological processes, as it has been demonstrated that losses, compared to equivalent wins, have larger effects on physiological arousal (Hochman & Yechiam, 2011). Hochman and Yechiam (2011) reported significantly larger pupil diameter and increased heart rate in response to losses compared to equivalent sized wins.…”
Section: Asymmetrical Impact Of Gains and Losses On Cognition And Behmentioning
confidence: 85%
“…Hochman and Yechiam (2011) reported significantly larger pupil diameter and increased heart rate in response to losses compared to equivalent sized wins. Recent MRI evidence from Dong, Lin, Hu, and Lu (2013) found that the experience of loss, compared to wins in a gambling task, caused more intense activity in the right superior temporal gyrus, bilateral superior frontal gyrus, bilateral anterior cingulate, bilateral insula cortex, and left orbitofrontal cortex; areas associated with the reward system in the brain (Dong, Lin, Hu, & Lu, 2013).…”
Section: Asymmetrical Impact Of Gains and Losses On Cognition And Behmentioning
confidence: 91%
“…If one attaches to the continuation or intensification of a joyful experience, then when this experience inevitably changes, one experiences dissatisfaction in proportion to the strength of the attachment (Bodhi 2006). Further, psychological studies have indicated that losses result in a larger physiological arousal than gains (Hochman and Yechiam 2011;Yechiam and Hochman 2013).…”
Section: Three Characteristics Of Existencementioning
confidence: 99%